Investor Sentiment and Stock Market Reactions: A Behavioral Economics Perspective - Baxi, Paramjit; Mishra, Smita; Asbe, Dr. Chetana; Mishra , Dr. Santosh Kumar; Meera , Dr.A.; Karthikeyan , M.P.; Mittal, Sachin (International Journal of Accounting and Economics Studies, 2025)
Investor sentiment plays a crucial role in behavioural finance. It’s essentially the theory behind how individuals form their beliefs about the market and the future prices of securities. When it comes to trading, individual investors are often swayed by sentiment much more than institutional traders, who typically rely on financial analysis. Many believe that individual investors tend to trade based on noise—information that might not be rooted in fundamental facts but rather in historical data or sensational news. Individual investors often fall prey to biases in their judgment, leading them to make similar mistakes, which can result in persistent market inefficiencies. While the significance of individual investor sentiment is clear, understanding how it’s shaped and which factors have a major influence on it is essential for both academics and practitioners looking to evaluate market efficiency. Understanding what drives investor sentiment is crucial because it plays a significant role in how stock prices move. Even though we recognize its importance and the complex nature of investor sentiment, we haven't thoroughly examined the factors that shape it or how they rank in significance. This research aims to gather and analyse data from individual investors to gauge their sentiment. The results could offer valuable insights for policymakers and contribute to the growing body of knowledge in behavioural finance.